PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPS KELAS VII DI SMP NEGERI 14 JAKARTA - Erliana Dwi Mutiara; Desy Safitri; Shahibah Yuliani (STKIP Subang, 2025)
The objective of the research is to analyze the influence of the Project Based Learning model on the social studies learning outcomes of seventh-grade students at SMP Negeri 14 Jakarta. The approach used is quantitative with a quasi-experimental method. The research population includes all seventh-grade students of SMP Negeri 14 Jakarta, consisting of 138 students from a total of four classes. The sample selection was conducted using random sampling, with class VII-A as the experimental class and VII-D as the control class. The data collection instrument was a written test in the form of multiple-choice questions used to measure learning outcomes. Based on the results of descriptive statistics, the average Pre-test score was 71.78 (experiment) and 71.69 (control), while the average Post-test score was 82.58 (experiment) and 73.31 (control). It can be concluded that the average score of the experimental group, which applied the project-based learning model, was higher than the average score of the control group, which only applied the conventional learning method. The results of the data test using the Independent Samples T-test with a Sig. (2-tailed) value of 0.016 < 0.05 indicate that the decision to reject and accept is based on this. Thus, there is a significant difference between the experimental class and the control class.